JURIDICAL ANALYSIS OF MARRIAGE DISPENSATION IN EARLY MARRIAGE (Case Study Of Decision Number 0022/Pdt.P/2023/PA.Pwt) - R.Fahmi Natigor Daulay; Beverly Evangelista (NOMOI Law Review, 2026)
Early marriage remains a serious problem in Indonesia despite Law Number 16 of 2019 establishing the marriage age limit at 19 years. This normative juridical research analyzes the regulation of marriage age restrictions, marriage dispensation mechanisms, and judicial considerations through a case study of Decision Number 0022/Pdt.P/2023/PA.Pwt. Research findings indicate inconsistencies in the application of marriage dispensation requirements in courts. Judges granted dispensation based on considerations of preventing adultery without examining aspects of the child's best interest in accordance with Supreme Court Regulation Number 5 of 2019. The significant age disparity between prospective spouses (more than 16 years) that potentially creates unequal power relations was disregarded. The research concludes that implementation of the child's best interest principle in marriage dispensation has not been optimal. Recommendations include tightening criteria for urgent reasons, strengthening judge training, and enhancing inter-agency coordination to effectively prevent child marriage.